2002
DOI: 10.1093/molehr/8.12.1136
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis for beta-thalassaemia using sequencing of single cell PCR products to detect mutations and polymorphic loci

Abstract: In order to carry out preimplantation genetic diagnosis (PGD) for beta-thalassaemia, we have applied direct sequencing of single cell PCR products to detect mutations and polymorphic loci within the beta-globin gene. Conventional duplex PCR was used to amplify two regions of the beta-globin gene with an amplification efficiency of 79% for blastomeres. Sequencing data were obtained for 100% of amplified products, with 12% having confirmed allele drop-out (ADO). A double ADO event was observed at least twice, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…The trials using single lymphocytes from an individual heterozygous for a b-thalassemia mutation and compound heterozygous at both microsatellite loci, demonstrated that the optimized protocol had a PCR success of almost 99% and an ADO rate of around 1% for all loci. These results compare favorably to all previous methods described for PGD for hemoglobin disorders, which report PCR success ranging between 87 to 99% and ADO of 0 to 12% for the b-globin gene locus [Holding and Monk, 1989;Monk and Holding, 1990;Varawalla et al, 1991;Ray et al, 1996;El-Hashemite et al, 1997;Kuliev et al, 1998;Vrettou et al, 1999;De Rycke et al, 2001;Piyamongkol et al, 2001;Hussey et al, 2002], and they are well within the limits generally set by centers offering PGD [ESHRE PGD Consortium Steering Committee, 2002]. As mentioned above, the occurrence of ADO will not lead to transfer of an affected embryo by the real-time genotyping method, although it may lead to risk of rejecting a heterozygous embryo.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The trials using single lymphocytes from an individual heterozygous for a b-thalassemia mutation and compound heterozygous at both microsatellite loci, demonstrated that the optimized protocol had a PCR success of almost 99% and an ADO rate of around 1% for all loci. These results compare favorably to all previous methods described for PGD for hemoglobin disorders, which report PCR success ranging between 87 to 99% and ADO of 0 to 12% for the b-globin gene locus [Holding and Monk, 1989;Monk and Holding, 1990;Varawalla et al, 1991;Ray et al, 1996;El-Hashemite et al, 1997;Kuliev et al, 1998;Vrettou et al, 1999;De Rycke et al, 2001;Piyamongkol et al, 2001;Hussey et al, 2002], and they are well within the limits generally set by centers offering PGD [ESHRE PGD Consortium Steering Committee, 2002]. As mentioned above, the occurrence of ADO will not lead to transfer of an affected embryo by the real-time genotyping method, although it may lead to risk of rejecting a heterozygous embryo.…”
Section: Discussionsupporting
confidence: 77%
“…In the cohort of blastomeres that were analyzed, a b-globin genotype was achieved in 92% of cells, again comparing favorably to previous reports of clinical PGD cycles [Ray et al, 1996;Kuliev et al, 1998;Kanavakis et al, 1999;De Rycke et al, 2001;Hussey et al, 2002] and improved relative to a rate of 78% PCR success when genotyping single blastomeres using our previously described nested PCR/DGGE method TraegerSynodinos et al, 2003]. It is more difficult to evaluate ADO in clinical PGD cycles, unless it presents as an impossible b-globin genotype based on the parental mutations in each cycle.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The remaining cases are due to point mutation (25-30%) [16] or duplications (5-10%) [5,17], but there have been no reports of PGD for DMD to the best of our knowledge. PGD for point mutation was performed for familial amyloidotic polyneuropathy (FAP) by nested PCR and single-stranded conformational polymorphism (SSCP) analysis [18], and for β-thalassaemia using sequencing of single cell PCR products [19]. Meanwhile, only a few reports exist concerning PGD for duplications [20,21], of which the detection is commonly possible using DNA probes located in the duplicated region (FISH or Southern blotting method).…”
Section: Introductionmentioning
confidence: 99%